The Improvement of Food Additives and Good Food Production Method Knowledge on Sumba Island - Noor Erma Nasution Sugijanto; Juni Ekowati; Heinrich Dengi; Asri Darmawati; Dewi Isadiartuti; Catur Dian Setiawan; Diajeng Putri Paramita; Melanny Ika Sulistyowati; Putri Hamidah Khairunnisa; Imamatin Nufus Melania; Muhammad Ilham Royyan Nafi; Sugijanto Kartosentono (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
In order to ensure good health and well-being in the community during the pandemic, especially in the food business in Sumba, several problems for MSME partners have been identified, namely related to food production, consumption, and misunderstanding of regulations in the food and beverage business which can be a problem for the health community. The solutions offered to overcome these problems are training in webinars and talk shows on Food Business Production Orders; Knowledge of Food Additives; Good Food Production Methods; Household Food Industry Product Licensing (CPPB-IRT); and Simple Marketing for the Food Business. This community service aims to improve MSMEs' quality and business capacity on Sumba Island, which is increasing and has become a model for similar MSME communities because they have not received similar guidance from any agency. The pre and post-test analysis results showed an increase in knowledge, especially on aspects of the types of food that were not allowed to receive SPP-IRT, food coloring, permitted food additives, how to get Halal certification, and spot tests to find out hazardous materials. The implementation evaluation showed that more than 58% stated that the material was acceptable. More than 99% stated that the registration was carried out well. For delivering materials and discussions, 99% said they were delighted. This webinar activity concludes that the material topics have been as needed, there is an increase in partner knowledge, and the implementation has been carried out well, based on pre-post test evaluation data and evaluation of the implementation of activities agency.